Soil microbes become a major pool of biological phosphorus during the early stage of soil development with little evidence of competition for phosphorus with plants - Wang, Jipeng; Wu, Yanhong; Zhou, Jun; Bing, Haijian; Sun, Hongyang; He, Qingqing; Li, Jingji; Wilcke, Wolfgang (Plant and soil, 2020)
Aims We aimed to quantify the pool size of soil microbial biomass P (P mic ) during the early stage of soil development up to 125 years after glacial retreat in the Gongga Mountains, China and relate the pool size of P mic to the plant P (P plant ) pools in the ecosystem. Methods We determined the pool sizes of P in soil microbes, plants and soils and the P fluxes with plant uptake and litterfall in successional ecosystems at five study sites along the 125-year Hailuogou glacial retreat chronosequence. Moreover, we estimated the flux of P cycled through microbial biomass (P mic cycling) based on literature data. We also approached the likelihood of P competition between plants and soil microbes based on the P status of the plants, soils and soil microbes. Results The size of the P mic pools (0.2–8.3 g m −2 ) in the organic layer and top 10 cm of the mineral soils was comparable to that of the P plant pools (0.3–9.1 g m −2 ) at all study sites along the Hailuogou chronosequence. Based on the literature, the P mic cycling at our study site (0.3–13.5 g m −2 year −1 if estimated based on temporal fluctuations of P mic , 5.2–268 g m −2 year −1 if estimated based on the isotope dilution method) was at least one order of magnitude larger than the P plant uptake (not detected-0.36 g m −2 year −1 ) and the P plant return by litterfall (not detected-0.16 g m −2 year −1 ). Although P mic became a major pool of biological P, we did not find indications of P competition between plants and soil microbes as indicated by the positive relationships between the concentrations of P mic and plant-available P in soils and the P-rich status of plants and soil microbes. Conclusions Soil microbial biomass already becomes a major P pool in the early stage of soil development. Our estimations based on the literature suggest that P mic cycling is probably the largest P flux in the studied up to 125-year ecosystems. Plants likely did not suffer P competition with microbes, in part due to the preferential decomposition of the P-rich compounds from dead microbial biomass which led to net P mineralization.